2020
DOI: 10.1042/bsr20202384
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of DNA methylation and gene expression profiles identified S100A9 as a potential biomarker in ulcerative colitis

Abstract: Ulcerative colitis (UC) is a prevalent relapsing-remitting inflammatory bowel disease whose pathogenetic mechanisms remain elusive. In the present study, colonic biopsies samples from three UC patients treated in the Traditional Chinese Medicine Hospital and three healthy controls were obtained. The genome-wide mRNA and lncRNA expression of the samples were profiled through Agilent gene expression microarray. Moreover, the genome-wide DNA methylation dataset of normal and UC colon tissues was also downloaded f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…These inflammatory complexes serve as pivotal components within multi-protein oligomer structures and innate immune networks, becoming engaged in 'aseptic' inflammatory responses triggered by damage-related molecular patterns (DAMPs) [ 28 , 29 ]. Studies have elucidated that S100A9 not only displays elevated levels in inflammatory conditions like inflammatory bowel disease, systemic lupus erythematosus, and rheumatoid arthritis, but it also exhibits a close association with numerous neurodegenerative diseases of the central nervous system [ [30] , [31] , [32] , [33] ]. Within the domain of renal diseases, Yang et al [ 34 ] identified the S100a9 hi Ly6c hi IMs population as early responders in acute kidney injury (AKI).…”
Section: Discussionmentioning
confidence: 99%
“…These inflammatory complexes serve as pivotal components within multi-protein oligomer structures and innate immune networks, becoming engaged in 'aseptic' inflammatory responses triggered by damage-related molecular patterns (DAMPs) [ 28 , 29 ]. Studies have elucidated that S100A9 not only displays elevated levels in inflammatory conditions like inflammatory bowel disease, systemic lupus erythematosus, and rheumatoid arthritis, but it also exhibits a close association with numerous neurodegenerative diseases of the central nervous system [ [30] , [31] , [32] , [33] ]. Within the domain of renal diseases, Yang et al [ 34 ] identified the S100a9 hi Ly6c hi IMs population as early responders in acute kidney injury (AKI).…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 ] Lawrance IC et al [ 26 ] proposed the elevated expression of S100A9 in UC for the first time, which was consistent with several studies including ours. [ 27 , 28 ] Calprotectin is a unique heterodimer of S100A8 and S100A9, which are two S100 EF-hand calcium binding proteins. Mortensen JH et al [ 29 ] found out that there was an association between neutrophil activity and endoscopic severity from patients with inflammatory bowel disease and a specific calprotectin epitope in serum, CPA9-HNE.…”
Section: Discussionmentioning
confidence: 99%
“…These autoimmune diseases responsible genes might be critical for the development of CD. Recently, study found that CXCL5 [454], S100A12 [455], OSM (oncostatin M) [456], LRG1 [457], LCN2 [458], CXCL1 [459], S100A9 [460], IFITM1 [461], XBP1 [462], MMP3 [457], IFITM3 [463], IL1B [464], GBP5 [465], HGF (hepatocyte growth factor) [466], CXCL9 [467], SLC11A1 [468], IL1RN [469], STAT1 [470], CYP27B1 [471], MMP1 [472], SOCS3 [473], TLR8 [474], CD55 [475], CCL28 [476], FCGR2A [477], CCL2 [478], CFB (complement factor B) [479], CD14 [480], GPR84 [481], PCSK9 [482], FOXP3 [483], LPL (lipoprotein lipase) [484], IL1R2 [485], TLR2 [486], MEFV (MEFV innate immuity regulator, pyrin) [487], VWF (von Willebrand factor) [488], NOD2 [489], DMBT1 [490], HSPA6 [491], TIMP1 [492], ICAM1 [493], EGR1 [494], CCL11 [495], IFNG (interferon gamma) [496], APOE (apolipoprotein E) [497] FGR (FGR proto-oncogene, Src family tyrosine kinase) [498], IL6 [499], SPP1 [192], IL11 [500], RNF186 [501], MMP2 [502], CD24 [503], SPHK1 [504], GZMB (granzyme B) [505], MUC5AC [506], SERPINA3 [507], TWIST1 [508], PLAU (plasminogen activator, urokinase) [509], CA2 [510], CA9 [510], CTLA4 [511], PADI4 [512], MMP13 [513], MPO (myeloperoxidase) [244], LEFTY1 [514], CA1 [515], MMP7 [513], ABCG2 [516], CYP2J2 [517], AICDA (activation induced cytidine deaminase) [518], CYP2D6 [519], CYP3A5 [52...…”
Section: Discussionmentioning
confidence: 99%